Analyzing Balance Sheet Vulnerabilities in a Dollarized Economy : The Case of Georgia - Billmeier, Andreas; Mathisen, Johan (Washington, D.C. : International Monetary Fund, 2006)
Balance-sheet analysis (BSA) complements traditional flow-oriented macroeconomic analysis by gauging mismatches in aggregate and sectoral balance sheets of an economy. Enabled by recent progress in data availability, this paper applies BSA to Georgia, focusing on currency mismatches. In reviewing developments over the last five years, the paper finds that the still-high level of dollarization continues to create financial vulnerabilities, but that the overall level of currency mismatch has fallen and that liquidity problems are unlikely, in part owing to a strengthening of sectoral buffers, hedges, and insurance against shocks. Policy recommendations include accumulating reserves, strengthening securities markets, enhancing banking supervision, and maintaining a flexible exchange rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet